Exploring soil microbial 16S rRNA sequence data to increase carbon yield and nitrogen efficiency of a bioenergy crop. Issue 5 (2nd July 2015) - Pitombo, Leonardo M.; do Carmo, Janaína B.; de Hollander, Mattias; Rossetto, Raffaella; López, Maryeimy V.; Cantarella, Heitor; Kuramae, Eiko E.
Abstract: Crop residues returned to the soil are important for the preservation of soil quality, health, and biodiversity, and they increase agriculture sustainability by recycling nutrients. Sugarcane is a bioenergy crop that produces huge amounts of straw (also known as trash) every year. In addition to straw, the ethanol industry also generates large volumes of vinasse, a liquid residue of ethanol production, which is recycled in sugarcane fields as fertilizer. However, both straw and vinasse have an impact on N2 O fluxes from the soil. Nitrous oxide is a greenhouse gas that is a primary concern in biofuel sustainability. Because bacteria and archaea are the main drivers of N redox processes in soil, in this study we propose the identification of taxa related with N2 O fluxes by combining functional responses (N2 O release) and the abundance of these microorganisms in soil. Using a large‐scale in situ experiment with ten treatments, an intensive gas monitoring approach, high‐throughput sequencing of soil microbial 16S rRNA gene and powerful statistical methods, we identified microbes related to N2 O fluxes in soil with sugarcane crops. In addition to the classical denitrifiers, we identified taxa within the phylum Firmicutes and mostly uncharacterized taxa recently described as important drivers of N2 O consumption. Treatments with straw and vinasse also allowed the identification of taxa with potential biotechnological properties that might improve the sustainability of bioethanol by increasing C yields and improving N efficiency in sugarcane fields.